2020
DOI: 10.21203/rs.3.rs-34844/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transnational Migration Aspirations, Educational Capabilities, Marriage Preferences, and Health Outcomes: A Mixed-Methods Study Among Pakistani youth

Abstract: Background: Pakistani youths desire for international migration due to the more favourable socioeconomic circumstances in the country of destination. This may lead to migration marriages among partners of mismatching socio-economic statuses. This study aims to analyse the migration aspirations in relation with educational capabilities, marriage preferences, and health outcomes in the context of an anticipated transnational migration. Methods: A sequential mixed-methods study has been conducted. Nine case studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
3
1
Order By: Relevance
“…In a previously conducted research it was found out that the respondents were ready to compromise on social status, attractiveness, love, and trustworthiness to marry a person who can serve as means of migration/settled (Jalil & Fischer, 2020). However, this is in contrast with our findings where only 14.3% of the sample preferred marrying a person who lived abroad because they do not want to be distant from their families, friends and culture.…”
Section: Discussioncontrasting
confidence: 97%
“…In a previously conducted research it was found out that the respondents were ready to compromise on social status, attractiveness, love, and trustworthiness to marry a person who can serve as means of migration/settled (Jalil & Fischer, 2020). However, this is in contrast with our findings where only 14.3% of the sample preferred marrying a person who lived abroad because they do not want to be distant from their families, friends and culture.…”
Section: Discussioncontrasting
confidence: 97%
“…Lastly, migrating for education is relatively common within Mexico (Valentine et al 2016;Ducoing Watty 2018;Jalil and Fischer 2020), and higher education levels are associated with delayed union formation (White and Potter 2013;Kroeger, Frank, and Schmeer 2015). I hypothesize that adolescent educational aspirations will account for some of the positive association between migration aspirations and the desired age at marriage (H3).…”
Section: Current Studymentioning
confidence: 99%
“…Migration intentions and aspirations are informed by various factors, including gender norms, family norms about migration, community exposure to migration, financial need, and social capital (De Jong 2000;Creighton 2013;Boccagni 2017;Jalil and Fischer 2020). Individuals who aspire to migrate are more likely to actually do so than those who do not have concrete intentions to migrate, controlling for the structural conditions that make realizing migration aspirations possible (Carling and Schewel 2018).…”
Section: Adolescent Migration Aspirationsmentioning
confidence: 99%
See 1 more Smart Citation